PENGARUH INVESTASI, PRODUK DOMESTIK REGIONAL BRUTO, DAN BELANJA MODAL TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN SUKOHARJO - Anita Ika Novita, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2016)
The purpose of this research is to know the influence of partially and simultaneous investments, gross Regional domestic product, and capital expenditure against Original Income areas in Sukoharjo Regency 2004-2014. Research methods method using case studies, the data type of the data being used is qualitative and quantitative data, the source data used the data of skunder. Method of data collection used documentation. Technique of data analysis used a classic assumption test, multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained conclusions: 1) there is a positive and significant influence investments against the original Revenue areas in Sukoharjo Regency. 2) there is a significant and positive influence on the gross Regional domestic product against Original Income areas in Sukoharjo Regency. There is a positive influence and significant capital expenditures against the original Revenue areas in Sukoharjo Regency. F test analysis results obtained the conclusion there is a significant influence of the free variables, namely investment, gross Regional domestic product expenditures simultaneously against a variable bound to the original Income i.e. the area in Sukoharjo Regency.Keywords: investment, gross regional domestic product, capital expenditures, income of the original area